University Social Responsibilities-Based Green Accounting: Implementation of Green Universities - Dwi Suhartini; Astrini Aning Widoretno; Rizdina Azmiyanti (Universitas Hayam Wuruk Perbanas, 2023)
The research aims to examine the differences in the implementation of green accounting based on University Social Responsibilities (USR) at the Sepuluh Nopember Institute of Technology (ITS) and Brawijaya University (UB). The data analysis method uses a different test approach with a sample size of 150 respondents from the academic community. The data collection method uses a mail survey with Google Forms. The research results prove no difference in implementing environmental awareness, environmental involvement, environmental reporting, environmental audit, and university social responsibility at ITS and UB. UB initiated the green campus concept and ITS with the eco campus concept. However, there are no audit reports related to green accounting at either campus. The contribution of this research will lead to policies for drafting environmental audit report regulations because campuses also produce waste from the impact of their activities. This regulation can strengthen sustainable practices on campus environments in Indonesia and ensure a sustainable environmental legacy for future generations.